System Analysis: Theory and Applications - Zgurovsky, Mikhail Z.; Pankratova, N.D (Data and Knowledge in a Changing World, 2007)
The foundations of system analysis as an applied scientific methodology assigned for the investigation of complex and highly interdisciplinary problems are provided in this monograph. The basic definitions and the methodological and theoretical basis of formalization and solution processes in various subject domains are presented. The methods of formalizing the system tasks and reducing them to a solvable form under real-world conditions and by taking into account e.g. sets of contradictory purposes, quantitative and qualitative characteristics of information, different kinds of uncertainties and risks are described in detail. In addition, the authors propose methods for disclosing the conceptual uncertainty and develop a strategy for system interaction or counteraction of coalitions under multifactorial risks. All these topics are supported by the presentation of computing algorithms and solution procedures for practical problems in socio-economics and in technology, e.g. for designing complex interconnected systems to function under the conditions of uncertainty and risk. This monograph will be useful to researcher, post-graduates and advanced students spezializing in system analysis, decision making, strategic planning or engineering design.